KEPUASAN KONSUMEN PADA DEPOT AIR MINUM ISI ULANG DI SEKOLAQ MULIAQ KABUPATEN KUTAI BARAT - Elfreda Aplonia Lau, Tania Widarti, Theresia Militina (EKONOMIA, 2016)
The research objective of this thesis was to determine whether or not the Customer Satisfaction effect on Enterprises (Company) Drinking water depots refills in Kampung Sekolaq Muliaq West Kutai. And to determine which factors are more influential among the service quality and marketing communications to customer satisfaction at Drinking Water Depot Refill in Kampung Sekolaq Muliaq RT. III West Kutai.The hypothesis of this research are: that the marketing communication significantly affect customer satisfaction, the second that service quality significantly affect customer satisfaction and the third that the quality of service of the dominant influence on customer satisfaction at Depot refill drinking water in Sekolaq Muliaq West Kutai.The sample in this research is the customer Depot Selly refill drinking water of 60 respondents through the questionnaire technique.The theory use, namely, marketing management which includes marketing communications, quality of service and customer satisfaction.The analytical tool used is using multiple linear regressionanalysis. Results of the analysis showed marketing communications and service quality are equally significant influence on customer satisfaction in drinking water refill depots in Sekolaq Muliaq West Kutai.While the quality of service the dominant influence on customer satisfaction at Drinking Water Depot Refill in Sekolaq Muliaq West Kutai.